Penggunaan Algoritma Backtracking Pada Permainan Knight's Tour Dengan Membandingkan Algoritma BFS Dan DFS - Refan Rahmat Fauzi; Mochammad Taufik Faturrohman; Raihan Samhari (Lembaga Pengembangan Kinerja Dosen, 2023)
Knight is one type of pawn in the game of chess. By using a strategy to play chess pieces, the rules of the Knight's Tour are formed. Knight's Tour is a math puzzle where we have to move the piece by forming the letter